2019
DOI: 10.3389/fneur.2019.00378
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Tract Alterations in Drug-Naïve Parkinson's Disease Patients With Excessive Daytime Sleepiness

Abstract: Excessive daytime sleepiness (EDS) is relatively frequent in patients with Parkinson's disease (PD), having a prominent burden on patients' quality of life and causing dangerous events such as motor-vehicle accidents. Previous studies have indicated the role of certain neural tracts in the pathophysiology of sleep disturbances, especially in PD patients. We hypothesized that white matter integrity and connectivity might be altered in patients with PD and EDS. Therefore, this study investigated brain white matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…We have previously demonstrated using resting state functional magnetic resonance imaging (rs-fMRI) decreased activation in the left cerebellum and inferior frontal gyrus, but increased activation in the left paracentral lobule in PD patients with EDS, compared with patients without EDS (Wen et al, 2016). A recent study using diffusion tensor imaging revealed that EDS in PD was associated with decreased microstructural connectivity in the fornices, inferior longitudinal fasciculi and cerebellar peduncles (Ashraf-Ganjouei et al, 2019). To date, there has not been a study examining the intrinsic neural network connectivity that underscores EDS in PD.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated using resting state functional magnetic resonance imaging (rs-fMRI) decreased activation in the left cerebellum and inferior frontal gyrus, but increased activation in the left paracentral lobule in PD patients with EDS, compared with patients without EDS (Wen et al, 2016). A recent study using diffusion tensor imaging revealed that EDS in PD was associated with decreased microstructural connectivity in the fornices, inferior longitudinal fasciculi and cerebellar peduncles (Ashraf-Ganjouei et al, 2019). To date, there has not been a study examining the intrinsic neural network connectivity that underscores EDS in PD.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of correlation between EDS and disease severity of PD [Hoehn & Yahr stage (H&Y)] has led to the notion that the EDS might be associated with PD-specific pathology (Yousaf et al, 2018b). However, in vivo neuroimaging quantification has been used to detect early pathophysiological changes in PD with EDS (PD-EDS), potentially serving as a biomarker for disease progression and treatment monitoring (Chondrogiorgi et al, 2016;Wen et al, 2017;Ashraf-Ganjouei et al, 2019). Molecular imaging studies using positron emission tomography (PET) and single-photon emission computed tomography (SPECT) implicate EDS with dopaminergic dysfunction in subcortical regions (Happe et al, 2007;Pagano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Levodopa‐equivalent dose was the only predictor of EDS development, whereas the dopamine‐agonist dose was the only predictor of EDS severity . On the other hand, very recently, microstructural abnormalities in drug‐naive PD patients with EDS involving the fornix, inferior longitudinal fasciculus, and inferior and middle cerebellar peduncles have been found, suggesting that EDS also could occur in the early stage of PD and without the influence of dopaminergic therapy . Accordingly, using resting‐state fMRI, Wen and colleagues showed widespread abnormalities in functional connectivity in drug‐naive PD patients with EDS compared with patients without, suggesting the presence of neural downregulation and compensatory mechanisms even at an early stage of disease.…”
Section: Resultsmentioning
confidence: 99%